2021
DOI: 10.25259/sni_29_2021
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of spinal infections managed by minimal debridement: A case series in two tertiary centers

Abstract: Background: Spinal infections can be challenging in their management and include spondylitis, epidural abscess, and spondylodiscitis. Usual treatment is conservative through antimicrobials or surgery to decompress neural tissue, debride all infected tissues, and fix if needed. We propose the concept of surgery without formal debridement aiming at neural protection. Methods: The study was performed at two tertiary centers on 25 patients with clinical findings. One patient was treated conservatively and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…[2] Turel et al mentioned the role of minimally invasive spine surgery in the management of pyogenic spinal discitis and all his patients had excellent recovery. [25] In our surgical strategy, we debrided the infected tissue as we can to help in eradication of infection, good neural tissue decompression, decreasing the recurrence, and obtaining proper fusion, in contrary, Mohamed et al did posterior fixation without debridement for vertebral body osteomyelitis and discitis only neurodecompression and as mentioned 14 patients were treated with posterior-only decompression and long-segment rigid fixation, without formal debridement of the infected area and reported that this strategy resulted in resolution of spinal infection in all cases and in significant neurological recovery in almost all cases. Blondel et al, 10 patients were included in this study and treated with a two-step procedure: posterior percutaneous osteosynthesis completed by complementary intervertebral grafting through an anterior access.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[2] Turel et al mentioned the role of minimally invasive spine surgery in the management of pyogenic spinal discitis and all his patients had excellent recovery. [25] In our surgical strategy, we debrided the infected tissue as we can to help in eradication of infection, good neural tissue decompression, decreasing the recurrence, and obtaining proper fusion, in contrary, Mohamed et al did posterior fixation without debridement for vertebral body osteomyelitis and discitis only neurodecompression and as mentioned 14 patients were treated with posterior-only decompression and long-segment rigid fixation, without formal debridement of the infected area and reported that this strategy resulted in resolution of spinal infection in all cases and in significant neurological recovery in almost all cases. Blondel et al, 10 patients were included in this study and treated with a two-step procedure: posterior percutaneous osteosynthesis completed by complementary intervertebral grafting through an anterior access.…”
Section: Discussionmentioning
confidence: 99%
“…Mohamed et al recorded single case of fixation looseness and another one for early superficial wound infection. [25] In Kamal et al, the wound healing problems occurred in one patient who originally underwent only drainage and debridement of infected/ necrotic tissue without instrumentation. [19] Faraj and Webb reported three patients developed deep wound infection, which responded to repeated debridement and they carried out all procedure redo for one patient with implant failure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation